2015
DOI: 10.5582/ddt.2015.01002
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm of serum 25 (OH) vitamin D, calcium and phosphorus levels in the treatment and management of type-2 diabetic patients

Abstract: The circadian time structure of serum 25 (OH) vitamin D (25-OHD), calcium (Ca) and phosphorus (P) may prove to be helpful in prevention, efficacy and management of diabetes mellitus. Ten newly diagnosed patients with type-2 diabetes mellitus (6 men and 4 women), 30-65 years of age, and 10 age-matched clinically healthy volunteers (7 men and 3 women) were synchronized for one week with diurnal activity from about 06:00 to about 22:00 and nocturnal rest. Breakfast was served around 08:00, lunch around 13:30 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 30 publications
3
25
0
1
Order By: Relevance
“…The increase in sCa above normal range was not associated with any adverse signs, and beyond 24 hours postdose, sCa returned to the normal range. The small fluctuations in sCa over the 96‐hour observation period mimics the pattern found in humans where the circadian acrophase of sCa in healthy individuals occurs around noon . The sP levels in the monkeys remained within the normal range after administration of both dose levels of TransCon PTH (data not shown).…”
Section: Resultssupporting
confidence: 64%
“…The increase in sCa above normal range was not associated with any adverse signs, and beyond 24 hours postdose, sCa returned to the normal range. The small fluctuations in sCa over the 96‐hour observation period mimics the pattern found in humans where the circadian acrophase of sCa in healthy individuals occurs around noon . The sP levels in the monkeys remained within the normal range after administration of both dose levels of TransCon PTH (data not shown).…”
Section: Resultssupporting
confidence: 64%
“…When daily central and peripheral rhythms are chronically disrupted or misaligned, the consequence of these circadian disruptions may be the development of metabolic disease [3]. Recent experimental studies [4,5,6] have suggested that the central circadian clock may also be regulated by another solar zeitgeber, vitamin D. Both 1,25-dihydroxycholecalciferol receptor (VDR) and 1α-hydroxylase (1α-OHase) were found to be widespread in human brain [4]. In adipose-derived stem cells, 1,25-dihydroxycholecalciferol was able to control the expression of circadian clock genes (i.e., BMAL1 and PER2) [5].…”
Section: Introductionmentioning
confidence: 99%
“…In adipose-derived stem cells, 1,25-dihydroxycholecalciferol was able to control the expression of circadian clock genes (i.e., BMAL1 and PER2) [5]. In addition, daily plasma 25-hydroxyvitamin D (25OHD) levels were reported to exhibit circadian oscillation [6]. Therefore, it is possible that vitamin D, otherwise known as the ‘sunshine vitamin’ [7], may influence circadian rhythms and related health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The HFnu was used to represent an index of parasympathetic activity, while the LFnu was used to represent an index of sympathetic activity in this study. AF episodes terminated during 06:00–22:00 represent diurnal events, and those during 22:00–06:00 represent nocturnal events . Decreased or increased LFnu and HFnu was defined as the data of the 0‐ to 5‐minute segment lower or higher than that of the 15‐ to 20‐minute segment.…”
Section: Methodsmentioning
confidence: 99%
“…AF episodes terminated during 06:00-22:00 represent diurnal events, and those during 22:00-06:00 represent nocturnal events. 17 Decreased or increased LFnu and HFnu was defined as the data of the 0-to 5-minute segment lower or higher than that of the 15-to 20-minute segment.…”
Section: Study Populationmentioning
confidence: 99%